“A word that describes it well is ‘lonely’” - experiencing preterm birth during the first COVID-19 lockdown in Germany: a qualitative study - Böhm-González, Simone Teresa; Detemple, Sarah; Gruß, Jasmin; Kribs, Angela; Berner-Rodoreda, Astrid; Härtel, Christoph; Dötsch, Jörg; Weyersberg, Annic (Early human development, 2025)
Background - During the first pandemic lockdown restrictive regulations were implemented in hospitals. Parents of preterm babies were particularly affected due to a long hospital stay. The aim of this study is to investigate how pandemic regulations during the first lockdown impacted the birth and perinatal experiences of parents of preterm babies. - Methods - For this qualitative study, we interviewed ten parents who had a preterm baby (28 to 32 gestational weeks) during the first lockdown in Germany. The interviews were analysed using reflexive thematic analysis. - Results - Five themes were identified 1) “Loneliness of pregnant mothers at risk at the maternity ward”, highlights the lack of physical and emotional support, intensified by a tense atmosphere at the hospitals 2) “Losing out on meaningful moments” describes the feeling of being cheated of a ‘real’ birth experience and missing out on the ‘normal life at home’ with a newborn 3) “Fear as a constant companion” refers to the fear of a COVID-19 infection during the hospital stay and ambivalent feelings upon arriving home 4) “Medical care of preterm infants during the pandemic” emphasizes the gaps in medical care of preterm infants but also underscores what went well despite pandemic restrictions and 5) “Mothers taking action to change hospital regulations” portrays their agency. - Conclusion - It is crucial to include scientific, pediatric expertise in future pandemic response planning to rapidly visualize and prevent negative consequences of mitigations measures, such as those described in this study. Protecting elements of family-centered and integrated care should be a priority.